Frequency and prognosis of associated malignancies in 504 patients with lymphomatoid papulosis. (5th December 2019) - Melchers, R.C.; Willemze, R.; Bekkenk, M.W.; de Haas, E.R.M.; Horvath, B.; van Rossum, M.M.; Sanders, C.J.G.; Veraart, J.C.J.M.; Putter, H.; Jansen, P.M.; Vermeer, M.H.; Quint, K.D.
Abstract: Background: Lymphomatoid papulosis (LyP) can be associated with other haematological malignancies (HM), but reported percentages vary from 20% to over 50%. Objective: To evaluate the frequency and prognostic significance of associated HM and non‐HM in LyP patients. Methods: In this multicentre cohort study, the complete Dutch LyP population was included from the Dutch Cutaneous Lymphoma Registry between 1985 and 2018. Clinical and histopathological information was retrieved from every individual patient. Results: After a median follow‐up of 120 months (range, 6–585), an associated HM was observed in 78/504 (15.5%) patients. Most common associated HM were mycosis fungoides (MF; n  = 31) and anaplastic large‐cell lymphoma (ALCL; n  = 29), while 19 patients had another HM of B‐cell ( n  = 14) or myeloid origin ( n  = 5). Even after a 25‐year follow‐up period, percentages of associated HM did not exceed 20%. Thirty‐nine of 465 patients (8.4%) without a prior or concurrent associated HM developed an associated HM during follow‐up, after a median of 68 months (range of 3–286 months). Nine of 78 patients died of associated HM, including 6/22 patients developing extracutaneous ALCL, while all patients with associated MF or skin‐limited ALCL had an excellent prognosis. Compared with the general population, LyP patients showed an increased risk (relative risk, 2.8; 95% confidence intervals, 2.4–3.3) for non‐HM, in particular cutaneous squamous cell carcinoma, melanoma and intestinal/lung/bladder cancer. Conclusions: An associated HM was reported in 15.5% of the LyP patients, particularly MF and ALCL. Although the frequency of associated HM is lower than suggested and the prognosis of most patients with associated HM is excellent, a small subgroup will develop aggressive disease, in particular extracutaneous ALCL. Furthermore, LyP patients have a higher risk of developing other malignancies. Clinicians should be aware of these risks, and LyP patients require close monitoring. Abstract : Linked article: F. Rongioletti. J Eur Acad Dermatol Venereol 2020; 34 : 216–217. https://doi.org/10.1111/jdv.16157 .